Implementing Context-Based Educational Interventions to Address Alternative Concepts of The Sun, Earth, and Moon Among Fifth-Grade Students - Altun, Yüksel; Sarı, Özge (GLOBETS 2023 Educational Technology and Science Research, 2024)
This study explores the efficacy of a context-based educational approach in elucidating and rectifying alternative conceptions among fifth-grade students concerning the astronomical subjects of the "Sun, Earth, and Moon." The research employed a mixed-methods approach, integrating structured and semi-structured interviews with pre-tests, post-tests, and retention tests to assess the students' conceptual understanding. The findings revealed that alternative conceptions were prevalent regarding the Earth's shape, the relative sizes of the Moon and Sun, the Earth's rotation and orbit, and the Moon's phases and structure. The study's context-based approach, aligned with contemporary educational theories, demonstrated significant effectiveness in addressing these alternative conceptions, enhancing students' conceptual understanding and retention. The research emphasizes the importance of context-based learning in scientific education and provides recommendations for curriculum development, teacher training, and future research directions.